Insight into the traditional timber frame walls: Herculaneum evidence versus braced frame structures in Portugal and in Italy - Stellacci, S. (2018)
In recent years there has been an increasing interest in the traditional timber frame constructions in earthquake prone areas, due to their good earthquake resistance and the remarkable architectural features. The purpose of this paper is to provide an insight into the historic timber frame walls and the reasons underpinning their use and dissemination within three different contexts, i.e. Herculaneum (until 79AD), Portugal and South of Italy (18th century). During the Roman Age, the large use of timber frame walls corresponds to a proactive approach to working within a project’s external constrains. Population growth and the need for fast and low-priced structures spurred an upgrade of construction techniques, especially in Herculaneum. After the macro-earthquakes in Portugal and in Italy, instead, a similar construction system, based on three-dimensional timber frames, is expressly employed for its seismic resistance. This diachronic comparison based on literature review and on-site analysis aims to clarify the influence of the timber frame walls on the architectural layout and on the building behaviour in these three case studies.